1989
DOI: 10.1007/bf00694339
|View full text |Cite
|
Sign up to set email alerts
|

Pharmacokinetics of busulfan: correlation with veno-occlusive disease in patients undergoing bone marrow transplantation

Abstract: Busulfan is an alkylating agent that is widely used in preparative regimens for bone marrow transplantation (BMT). We developed a high-performance liquid chromatographic (HPLC) assay for the determination of plasma busulfan concentrations in 30 patients who received oral doses of 1 mg/kg. Concentrations were fit by a one-compartment pharmacokinetic model with first-order absorption. The pattern of absorption and elimination varied widely between patients, with peak concentrations ranging from 1.2 to 10.4 mumol… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

9
234
1

Year Published

2000
2000
2016
2016

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 378 publications
(244 citation statements)
references
References 15 publications
9
234
1
Order By: Relevance
“…11 Targeted dose adjustment of BU to maintain the overall systemic exposure within a proper range may reduce these risks. [4][5][6][7]14,15 Although it has been reported that there are ethnic differences in PK for a wide range of drugs, 28 this has not been seriously examined with i.v. BU.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…11 Targeted dose adjustment of BU to maintain the overall systemic exposure within a proper range may reduce these risks. [4][5][6][7]14,15 Although it has been reported that there are ethnic differences in PK for a wide range of drugs, 28 this has not been seriously examined with i.v. BU.…”
Section: Discussionmentioning
confidence: 99%
“…1 To overcome the disadvantage of oral BU including gastrointestinal absorption, [2][3][4][5][6][7][8][9][10][11][12][13][14][15][16] i.v. BU was recently introduced into clinical use.…”
Section: Introductionmentioning
confidence: 99%
“…Renal elimination of Bu is known to be minor; about 2% of the unchanged drug is excreted in the urine [6,7]. The magnitude of inter-patient variation associated with oral Bu apparent clearance (CL/F) has been estimated at as high as 10-fold or more [7][8][9]. Patient characteristics and treatment co-factors have been studied for a better understanding of this high variability.…”
Section: Introductionmentioning
confidence: 99%
“…High values of areas under the plasma concentration-versus-time curve (AUC) have been related to an increased risk of severe regimen-related toxicities including hepatic veno-occlusive disease (VOD) [8,[12][13][14][15]. Conversely, low Bu AUCs have been correlated with an increased risk for graft rejection and leukaemia relapse.…”
Section: Introductionmentioning
confidence: 99%
“…Busulphanbased conditioning has previously been reported as the most important risk factor for VOD. 14 Wong et al 15 also found a 36% incidence of VOD in their series of 53 patients with myelofibrosis. As the FluBuATG regime is commonly used as the conditioning of choice for patients with myelofibrosis, 16 the risk of VOD in these patients is significantly increased.…”
mentioning
confidence: 89%